Methylation and dealkykation of tin compounds by sulfate- and nitrate-reducing bacteria - Bridou R. (2018)
In this study, axenic cultures of sulfate-reducing (SRB) and nitrate-reducing (NRB) bacteria were examined for their ability to methylate inorganic tin and to methylate or dealkylate butyltin compounds. Environmentally relevant concentrations of natural abundance tributyltin (TBT) and 116Sn-enriched inorganic tin were added to bacterial cultures to identify bacterial-mediated methylation and dealkylation reactions. The results show that none of the Desulfovibrio strains tested was able to induce any transformation process. In contrast, Desulfobulbus propionicus strain DSM-6523 degraded TBT either under sulfidogenic or non-sulfidogenic conditions. In addition, it was able to alkykate 116Sn-enriched inorganic tin leading to the formation of more toxic dimethyltin and trimethyltin. A similar capacity was observed for incubations of Pseudomonas but with a much greater dealkykation of TBT. As such, Pseudomonas sp. ADR42 degraded 61% of the initial TBT under aerobic conditions and 35% under nitrate-reducing conditions. This is the first work reporting a simultaneous TBT degradation and a methylation of both inorganic tin species and TBT dealkykation products by SRB and NRB under anoxic conditions. These reactions are environmentally relevant as they can control the mobility of these compounds in aquatic ecosystems; as well as their toxicity toward resident organisms. © 2018 Elsevier